Peningkatan Pemahaman Penyelesaian Kasus Penganiayaan dengan Konsep Restorative Justice di Masyarakat Kota Tanjungpinang: Pengabdian - Aris Bintania; Daria; Ibnu Arifin; Adidtya Syaputra (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This community service program was initiated in response to the limited understanding among village officials, community leaders, and local customary law groups in Tanjungpinang City regarding the implementation of Restorative Justice in resolving assault cases. This lack of understanding often results in conflict resolution processes that do not fully uphold the principles of justice and fail to provide legal certainty for the involved parties. The purpose of this program is to deliver education, assistance, and capacity-building for community members and grassroots-level law enforcers on the concept, legal foundation, and procedural stages of Restorative Justice. The methods employed include regulatory socialization, case-based training, focus group discussions (FGD), and simulation of restorative dispute-resolution practices. The results indicate a significant improvement in participants’ understanding of Restorative Justice principles, particularly regarding justice, voluntariness, and the stages of penal mediation. Participants were able to identify restorative steps in handling assault cases and relate them to the applicable legal regulations. However, the program also found that legal certainty remains a major challenge at the community level due to limited coordination with formal law enforcement agencies.